Geotechnical extreme-event reconnaissance (GEER) investigation to the 2016 Mw6.0, Mw6.2and Mw7.0 Kumamoto Japan Earthquakes - R. Kayen; T. Kokusho; H. Hazarika; S. Dashti; J. R. Calderon; T. K. Franke; N. K. Oettle; B. Wham; G.P. Louis-Kayen; R. Sitar; N.M. Louis-Kayen (International Association of Lowland Technology, 2018)
The Kumamoto, Kyushu, Japan earthquakes began with an earthquake (M6.2) on the Hinagu Fault on April 14, 2016 followed by a second (M7.0) event on the Futagawa Fault, that on April 16. These shallow 10-11 deep km events are the strongest earthquakes recorded in Kyushu prefecture during the modern instrumental era. The United States’ National Science Foundation (US NSF) supported Geotechnical Extreme Events Reconnaissance (GEER) Association conducted a reconnaissance of the region. These earthquakes resulted in substantial damage to infrastructure, buildings, cultural heritage of Kumamoto castle, roads and highways, slopes, and river embankments. Surface fault rupture produced offset to roads, buildings, river levees, and an agricultural dam. Surprisingly, given the extremely intense earthquake motions, liquefaction-induced damage was mostly limited to a few districts of Kumamoto City and in port areas, indicating that either the volcanic soils were largely unsusceptible to liquefaction or the presence of fines reduced the surficial manifestation of liquefaction and its effects. The important case histories identified by the study are [1] fault rupture through OhKirihata Dam; [2] subsidence in Aso Caldera; [3] fault rupture through Shimojin-Cho River Canal; [4] surprising paucity of liquefaction and its effects; and [5] possible identification of a nearly non-displacement lateral spread.